Analysis of Difficulties in Understanding the Work and Energy Concept of High School Students - Simamora, rikki_anita25 (Al-Khazini: Jurnal Pendidikan Fisika, 2024)
This study aims to determine the difficulty of understanding the concept of work and energy in high school students. This research uses descriptive with survey method with research data obtained from student test results. The instrument used is a questionnaire about the concept of work and energy. This research was conducted at SMAN 14 Medan Class XII IPA 4 and XII IPA 5 with the subject of 30 students who have learned the concept of work and energy. The difficulty of understanding the concept experienced by students is that students fall into the medium category in terms of understanding the concept of work and energy material in physics lessons with a percentage of 46.66%. As many as 33.33% of students have difficulty in analyzing effort (positive, negative or zero), kinetic energy, gravitational potential energy, and the law work. Students' difficulty in applying the concept of the law of work and energy in everyday life, amounting to 33.33%. The factors that cause difficulties in understanding the concepts experienced by students are caused by the way the teacher teaches and the students themselves. Keywords: Difficulties, Concept Understanding, Work and Energy